Reflective or Diffractive Learning/Teaching? Concurrences of Paul Ramsden And Karen Barad’s Approaches - Rybačiauskaitė, Karolina (Acta Paedagogica Vilnensia, 2020)
In this article it is argued that the optical metaphor and critical practice of diffraction further developed by Donna Haraway and Karen Barad might be no less significant than the widely spread notion of reflection, when the questions of various practices of knowledge are addressed. By considering Paul Ramsden’s approach to learning/teaching and its underlying theory in higher education alongside Karen Barad’s methodology of diffraction, it is shown that Ramsden’s understanding of learning/teaching is rather based on the theoretical assumptions of diffractive practice. His notion that teaching/learning are closely related and actively shaping each other, and that learners are not disconnected from the environment and their previous experiences with the subject matter and learning process itself, adds to Barad’s onto-epistemological position that knowers know the world at the same time as being the part of the world in its ongoing intra-activity. Ramsden’s understanding of relation is diffractive, because it is not about predefined binary entities and their fixed identities, but about layers and entanglements of various previous experiences and reactions to the learning environment. In addition, looking at learning/teaching processes through a different perspective also leads to a different approach to teaching and other ways of problem-solving. Both Ramsden and Barad distrust homologies, analogies, and causality-based conceptions of knowledge sharing. Instead, the ability to respond to an always new learning/teaching environment is assessed, which implies a diffractive type of sensitivity to the context, iterative process of re-turning, and the creation of dangerously indeterminate relationships and commitments. In this way, some of Barad’s philosophical notions, i.e., the diffraction pattern, intra-activity, re-turning, and others, also may acquire new practical content.
Keywords: Karen Barad; difrakcija; Donna Haraway; mokymas; mokymasis; aukštasis mokslas; refleksija; Paul Ramsden